Research on the Educational Pathways of Student Association Practices under the Rural Revitalization Strategy: An Analysis Based on the Marxist View of Practice - Zhang, Yufeng (Pacific International Journal, 2025)
Guided by the Marxist theory of practice, this study explores the educational logic and realization pathways embedded in university student association activities within the context of China’s national Rural Revitalization Strategy. The findings reveal that student associations, through multi-dimensional practices such as educational support, technological services, and cultural inheritance, not only respond effectively to the developmental needs of rural communities but also facilitate participants’ knowledge application, capacity enhancement, and value formation—thereby achieving a dialectical unity between social service and personal development. However, the study also identifies several challenges, including structural mismatches between service provision and rural needs, as well as tensions between cognitive enrichment and practical efficacy. To address these issues, this paper proposes the construction of an integrated practice-based education system, the deepening of collaborative education mechanisms through university–local partnerships, and the improvement of scientific and diversified evaluation and incentive systems. These measures aim to provide theoretical support and practical guidance for the high-quality development of practice-oriented education models.